STUDENTS' CRITICAL THINKING SKILLS ON THE USE OF FLIPBUILDER LEARNING MEDIA ENVIRONMENTAL CARE AND DISASTER RESPONSE BASED ON ISLAMIC VALUES: DOES IT AFFECT SOCIAL ATTITUDES AND RELIGIOUS TOLERANCE? - Nur Isroatul Khusna; Chusnul Chotimah; Luluk Atirotu Zahroh; Ikfi Khoulita (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Improving the quality of education in Indonesia is one of the challenges the government must solve. The ability to think critically about caring for the environment and disaster response is a significant issue. Students must master it because it will impact various aspects of life, such as social attitudes and religious tolerance. One solution is to provide the material using the innovative learning media, FlipBuilder. This study aims to determine the influence of critical thinking on social attitudes, assess the impact of essential thinking skills on religious tolerance attitudes, and find out the influence of critical thinking skills on students' religious tolerance attitudes when using flipbuilder learning media with the theme of environmental care and disaster response based on Islamic values. The research was conducted through a quantitative approach with an associative research design. The research was conducted on grade VII students of MTsN 1 Tulungagung. Data analysis was carried out using inferential statistics. The results of the study showed that there was a positive and significant influence between critical thinking skills and social attitudes, there was a positive and significant influence between essential skills of thinking and religious tolerance attitudes, and there was a significant relationship between social attitude variables and students' religious tolerance attitudes.